The impact of collaborative cues on perceived credibility of websites - Helen Nofrina (2009)
Recent technological advancements have helped give rise to a variety of websites offering user-generated content. Through the use of focus groups and an experiment, this study systematically examines how specific attributes of collaborative websites affect credibility judgments. From the focus groups, influential collaborative features identified were the editing features, discussion board and edit history. In addition, the presence of references was seen as an important factor which helps to enhance website credibility. Despite the perceived advantages of collaborative features such as unbiased and more up-to-date information, there were some concerns about possible vandalism and the inaccuracy of information. Based on the focus group findings, a between-subjects experimental study was conducted to examine the effect of the type of website and the presence of references on credibility assessment. The results show that there is no significant difference in site credibility between collaborative and non-collaborative websites, regardless of the presence of references. Further analyses suggest that collaborative cues may even have negative impact on the websites. From the experimental results, it was also found that the degree of involvement, prior knowledge of topic and time spent viewing the website were found to be positively related to site credibility. Similarly, the focus group results show that highly involved respondents also identified message characteristics as another factor influencing their credibility judgments. Nevertheless, the experiment findings suggest that the importance of collaborative features and references might have been overemphasized in the focus group discussions due to the setting encouraging participants to be mindful of their responses.